Rights of the buyer under The Sale of Goods in Shari‘ah and International Trade Law: a comparative analysis - Hassan, Mazin Abdulhameed Dawood; Ahmad Azam Othman (Pusat Penyelidikan Syariah, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2024)
The sale of goods is one of the most common transactions worldwide, practised by people to meet their various, ongoing, and daily needs. Consequently, buyers acquire certain rights against sellers, protected by applicable laws that may vary across jurisdictions. This paper aims to evaluate buyers’ rights under both Shari‘ah and international trade law. It examines these rights before and after the conclusion of a contract and then compares the two legal frameworks in this context. This research employs doctrinal and Islamic legal research methods, considering Shari‘ah and international trade law sources. Upon examination, it becomes evident that there are both similarities and differences between these two legal systems regarding the rights of buyers.